Surface Modification of Stainless Steel for Cavitation Environment Through Microwave Cladding - Mago, Jonty (My University, 2019)
The problem of cavitation in hydropower plant components is the major challenge. Surface modification is the most economical method to enhance material resistance for the cavitation prone components. However, poor adhesion, cracks, and porosity of cladding/coating deposited on the substrate material is the main limitation of the commonly used surface modification techniques. Cladding via microwave route is a potential surface modification technique to mitigate these defects. In the present study, the composite clads of Ni-based/40Cr3C2 and Ni-based/20Cr3C2-20Mo were successfully developed on SS-316 substrate via microwave cladding route after optimizing the processing parameters at 2.45 GHz frequency and 900 W power in a domestic microwave oven. The prepared clads were examined for microstructure, phase quality and quantity, porosity, microhardness, flexural strength (bonding strength) and cavitation erosion resistance at different parametric conditions. Whereas, the microstructural examination of the developed clads has been carried out by using scanning electron microscopy, the phase investigation has been carried by using X-ray diffraction (XRD), the microhardness measurement has been performed using Vicker’s microhardness tester. Whereas the porosity analysis, flexure strength test and cavitation erosion study have been performed as per ASTM-B276-05, ASTM-C1161-13 and ASTM-G32-16 standards, respectively. The microstructure analysis reveals that the composite clads of 600 μm and 750 μm thicknesses were developed and the developed clads are free from all type of visible cracks and pores. The stripe-like Cr3C2 and rib-like or net-like Mo precipitate were found through microstructural investigation. The results of porosity analysis show that the developed Ni-based/40Cr3C2 and Ni-based/20Cr3C2-20Mo composite clads possesses only 1.67 % and 0.26 %, which is significantly less as compared to conventionally used cladding/coatings processes. The XRD analysis confirms the presence of various possible intermetallics (Ni3Cr2, Ni3Fe, FeCr, FeMoCr, MoNi4) and hard carbide (Cr23C6, Cr3Ni2SiC, SiC, NiMo4C, Mo2C) phases in the clad region. The formation of various carbides, silicides and intermetallics during microwave hybrid heating led to higher microhardness of the developed composite clads. The microhardness of the developed Ni-based/40Cr3C2 and Ni-based/20Cr3C2-20Mo composite clad is come out to be 605±80 HV0.3 and 681±30 HV0.3, respectively, which is 3 and 3.5 times higher than that of the substrate (SS-316) respectively. The presence of high strength carbides and intermetallics in the microwave processed composite clads resulted in the higher flexural strength of these clads. The value of flexural strength in case of Ni-based/40Cr3C2 composite clad was 813.229 MPa. On the other hand, in case of Ni-based/20Cr3C2-20Mo, the flexural strength was 708.76 MPa. The functional characterization (in terms of vibratory cavitation erosion testing at varying test parameters) results revealed that cavitation erosion resistance (CER) of the developed composite clads is higher than the SS-304 substrate. The Ni-based/20Cr3C2- 20Mo composite exhibited better CER than all other developed clads. The overall results led to the conclusions that the microwave energy was successfully utilized to develop the CER clads of various materials. The microwave processed composite clads can be successfully used in hydropower plant applications.
Keywords: Microwave Cladding; Characterization; ASTM-G32; Cavitation Erosion Resistance; Flexure Strength; Fractographic Analysis